New directions in children's and adolescents' information behavior research - Beheshti, Jamshid, 1952-; Bilal, Dania, 1956- (Library and information science (New York, N.Y.), 2014)
Modern research shows that children and adolescents encounter challenges and obstacles in searching for information, retrieving relevant results and have difficulty interpreting results within various information environments. However, a recent paradigm shift points to the changed information behavior of the new generation of users, known now as "digital natives"; born after the advent of the Web. Technologically savvy, they skim and surf for information, multi-task, search collaboratively and share information on social networks. This book comprises innovative research in three main themes: information behavior of various age groups; special populations including ethnic minorities, indigenous peoples, and users with disabilities; research and reflections on designing systems that help the new generation cope with a complex knowledge society. The book is aimed directly at researchers who are aware of the challenges facing the new generation but have not had the opportunity to explore the issues thoroughly. It is also of interest to information professionals, librarians, educators, Web designers, and human-computer interaction researchers.